Shakespeare's heroines Characteristics of women: Moral, poetical and Historical - Jameson, Anna frey50 (A.L Burt Company New York)
"First published in 1832, Shakespeare's Heroines is a unique hybrid of Shakespeare criticism, women's rights activism, and conduct literature. Jameson's collection of readings of female characters includes praise for unexpected role models as varied as Portia, Cleopatra, and Lady Macbeth; her interpretations of these and other characters portray intellect, passion, political ambition, and eroticism as acceptable
Charecters of Intellect: Portia--Merchant of Vencie, Isabella--Measure for Measure, Beatruce--Much ado about nothing, Rosalined--As you like it --- Characters of Passion and Imagination: Juliet--Romero and Juliet, Helena--All's well that ends well, Perdita--A winter's tale, Viola--Twelth night, Ophelia--Hamlet, Miranda--Tempest --- Characters of affection: Hermione--A winter's tale, Desdemona--Othello, Imogen--Cymbeline, Cordelia--King Lear --- Historical Characters: Cleopatra--Antony and Cleopatra, Octoavia--Antony and Cleopatra, Volumnia-- Cariolanus, Constance--King John, Queen Elinor--King John, Blanche--King John, Margaret of Anjou--Henry VI, Queen Katherine of Arragon--Henry VIII, Lady Macbeth--Macbeth
Keywords: Shakespeare, William -- 1564-1616 -- Characters -- Women